ANALISIS PENGARUH PENDAPATAN BANK SYARIAH DAN PENDAPATAN BANK KONVENSIONAL TERHADAP PROFITABILITAS BANK (Studi Kasus Pada Bank BRI Syariah dan Bank BRI Umum) - Rizka Abdillah; Mukhlis M.Nur; Devi Andriyani (JURNAL EKONOMIKA INDONESIA, 2021)
This study aims to determine the effect of Islamic bank revenues and Conventional Bank Revenues on bank profitability (a case study at BRI Syariah and BRI Conventional). It uses scond data obtained by documentation and literature methods. The samples are quarterly data revenues received by BRI Syariah from 2012 to 2019, quarterly data of revenues received by BRI Conventional from 012 to 2019, and quarterly data on ROE of Bank BRI from 2012 to 2019. The data analysis program with the multilinear method regessionand with help of Eviews program. The results partially show that Islamic bank and conventional bank revenues doesn’t has significant profitability effect to profitability of Bank BRI. Simultaneously, Islamic bank and conventional bank revenues do not significantly influence Bank BRI profitability. The magnitude effect of Islamic bank and conventional bank revenues on Bank BRI profitability is 0.06 (6%), and the remaining 11-0. 06 = 0.94 (94%) can be explained outside of this research model.